1982
DOI: 10.1902/jop.1982.53.6.368
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Penetration Into Root Cementum of Periodontally Healthy and Diseased Human Teeth

Abstract: This study was undertaken to determine the extent of in vitro penetration of E. coli endotoxin into the root cementum of periodontally healthy and diseased teeth. Freshly extracted teeth were washed in distilled water, scaled and divided into two groups of 16 teeth each. Nine diseased and five healthy teeth in the first group were immersed in various concentrations of E. coli endotoxin for 2 to 12 weeks. They were then prepared for indirect immunofluorescence examination after treatment with anti‐endotoxin ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
8

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 18 publications
2
60
1
8
Order By: Relevance
“…Nakib et al 16 examined the range of penetration of endotoxin into the cementum and dentin. They reported surface adhesion of endotoxin, but found almost no deeper penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Nakib et al 16 examined the range of penetration of endotoxin into the cementum and dentin. They reported surface adhesion of endotoxin, but found almost no deeper penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Nakib, et al (1982) Commercially obtained endotoxin may not significantly affect the attachment of fibroblasts but may only affect their growth (Bergman and Nilsson, 1963;DeRenzis, 1981;and Olson, Adams and Layman, 1985) or both growth and viability (Aleo, et al 1974;Singer and Dutton, 1979).…”
mentioning
confidence: 99%
“…Nakib et al (21) demonstrated that LPS is only weakly bound to the root surface and can readily be brushed away.…”
Section: Resultsmentioning
confidence: 99%
“…Also, such studies demonstrated that cells can successfully attach to diseased cementum and suggested that the great amount of entodoxin was only superficially located at the diseased cementum (7,21).…”
Section: Introductionmentioning
confidence: 99%